Implementasi K13 dan Penyesuaian Terhadap Kurikulum Merdeka di SLB-A PRPCN Palembang - Astuti, Mardiah; Marlina, Leny; Saprullah, Saprullah; Irvan, Indra Ari; Fitrianti, Eka (Indo-MathEdu Intellectuals Journal, 2023)
Special needs education is education tailored to the physical, intellectual, emotional, and social needs of children. This research aims to investigate the implementation of the K-13 curriculum and its adaptation to the Merdeka Curriculum for Children with Special Needs at SLB-A PRPCN Palembang. The method employed is qualitative, involving data collection techniques through interviews, observations, and documentation. Data analysis techniques consist of data collection, data presentation, verification, and drawing conclusions. The data analysis results indicate that the school principal has successfully organized, provided guidance, motivation, and coordinated effectively with all educational stakeholders at SLB-A PRPCN, including teachers, staff, students, and parents as partners in the educational process. In this process, continuous efforts are necessary to enhance the implementation of the K-13 curriculum that has been adapted to the Merdeka curriculum for children with special needs. These efforts encompass improving teacher qualifications, enhancing learning facilities, and identifying and addressing factors that support or hinder curriculum implementation. It is expected that these actions will have a significant positive impact on the quality of education for children with special needs at SLB-A PRPCN Palembang